The source of a movement: making the case for social media as an informational source using Black Lives Matter. Issue 11 (2nd September 2017) - Cox, Jonathan M.
ABSTRACT: Social media is growing as a technological and social phenomenon, with billions of people using it every day around the world. Given its increasing ubiquity, researchers continue to seek to understand social media and its implications for the social world. Part of the growing body of scholarship on social media includes uncovering the most effective methodologies for exploration that appropriately consider differences between the technology of social media and the ways in which people use them. New directions for social media research include the use of big data and analysing the socio-technical nature of social media. Using data from an ongoing study on college Millennials that includes questions about their thoughts on the Black Lives Matter movement, the author suggests another direction for future research: studying the implications of social media as an informational source.